Poverty amongst coastal fishermen in Surabaya City, Indonesia - Dewi Casmiwati (2021)
The well-being of the fishing community has become one of the important agendas in the development of each country due to the poverty faced by this group. Therefore, this study aims to explore poverty among coastal fishermen in Surabaya as a whole. This study also identifies the contributing factors to poverty amongst coastal fishermen in Surabaya. Coping strategies and livelihood outcomes through the Social Safety Net amongst this group were also identified in the study. Poverty theory was used to answer the objectives of this study highlighted by Bradshaw (2006). While the approach by Moser (1998) and Haidar (2009) is also used in the implementation of coping strategies and livelihood outcomes of this group. Moreover, this research used a qualitative method with primary data collected from interviews and observations, and secondary data obtained from documentation and documentary reviews. Data were analyzed using thematic analysis based on theoretical paradigms and previous models. The results showed that the main factors that contributed to coastal fishermen's poverty in Surabaya City are politics, economics, and social conditions followed by natural factors, individual deficiency, the dependency between juragan and fishermen, and cultural factor. Meanwhile, the novelty of this thesis is that the dependency relationship between middle-man (juragan) and fishermen is mutually beneficial although middle-man (juragan) still gets benefits from the fishermen. Nevertheless, this research found that to face the difficulties of life, coastal fishermen in Surabaya City owe money to their neighbors, relatives and middle-man (juragan) as a coping strategy. Moreover, this research found that SSN has increased coastal fishermen's livelihood in Surabaya that includes increasing food supply (SSN-food aid), increasing income, education (SSN-education), and health (SSN-health). But the major problem of the SSN was only a few fishermen benefited from it. Therefore, this research provided recommendations to improve the human capital of fishermen by providing education and training, protect fishermen fishing area from the policy, strict environmental law enforcement, create partnerships between the government and middle-man (juragan) in terms of marketing fishes and increasing the number of SSN beneficiaries.